2009
DOI: 10.1098/rspb.2009.1222
|View full text |Cite
|
Sign up to set email alerts
|

Low-quality females prefer low-quality males when choosing a mate

Abstract: Mate choice studies routinely assume female preferences for indicators of high quality in males but rarely consider developmental causes of within-population variation in mating preferences. By contrast, recent mate choice models assume that costs and benefits of searching or competing for high-quality males depend on females' phenotypic quality. A prediction following from these models is that manipulation of female quality should alter her choosiness or even the direction of her mating preferences. We here p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
160
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 47 publications
(102 reference statements)
10
160
4
2
Order By: Relevance
“…just before fledging, growing up in a large brood resulted in 1.4 g (12%) lower mass without altering the variance (s.d. : 1.4 in both groups; n ¼ 478; electronic supplementary material, figure S1) in agreement with earlier reports [31,44]. Selective disappearance of low-quality individuals, reducing heterogeneity, can bias estimates of the long-term rspb.royalsocietypublishing.org Proc.…”
Section: Materials and Methods (A) Developmentsupporting
confidence: 89%
“…just before fledging, growing up in a large brood resulted in 1.4 g (12%) lower mass without altering the variance (s.d. : 1.4 in both groups; n ¼ 478; electronic supplementary material, figure S1) in agreement with earlier reports [31,44]. Selective disappearance of low-quality individuals, reducing heterogeneity, can bias estimates of the long-term rspb.royalsocietypublishing.org Proc.…”
Section: Materials and Methods (A) Developmentsupporting
confidence: 89%
“…In accordance with predictions of the differential allocation hypothesis (Sheldon, 2000), many previous studies in birds have reported that females paired with attractive or preferred males increased their reproductive investment by laying larger clutches or heavier eggs (e.g., peahen, Pavo cristatus: Petrie & Williams, 1993; Chinese quail, Coturnix chinensis: Uller et al, 2005; mallard, Anas platyrhynchos: Cunningham & Russell, 2000; zebra finch, Taeniopygia guttata: Balzer & Williams, 1998;Gilbert et al, 2006;Holveck & Riebel, 2010; canary, Serinus canaria: Leitner et al, 2006). In addition, it has been revealed that the attractiveness of mates affects the concentration of egg yolk components thought to contribute to the early physical development of offspring, such as testosterone (Gil et al, 1999;Gil et al, 2004; but see Mazuc et al, 2003;Michl et al, 2005) and immune factors (Saino et al, 2002b).…”
Section: Introductionsupporting
confidence: 65%
“…It is also possible that initial effects of brood size on personality related traits such as stress responses were leveled out by the standardized hand-rearing procedure from day 10 onwards. Indeed, most studies on long-term effects of early developmental stress manipulated conditions throughout the whole period of nutritional dependence (Brinkhof, Heeb, Kölliker, & Richner, 1999;Buchanan, Leitner, Spencer, Goldsmith, & Catchpole, 2004;Holveck & Riebel, 2010;Naguib, Riebel, Marzal, & Gil, 2004) so that comparatively little is known about long-term effects of only the early nestling period Honarmand et al, 2010;Krause et al, 2009).…”
Section: Discussionmentioning
confidence: 99%